One-Pot Synthesis of W-TiO2/SiO2 Catalysts for the Photodegradation of p-Nitrophenol - Ulises Arellano Sánchez; Lifang Chen; Jin An Wang; Luis Enrique Noreña; Maximiliano Asomoza; Silvia Solis; Xiaolong Zhou; Yueqin Song; Jing Liu (International Journal of Photoenergy)
Double modifications of TiO2 by doping with WO3 and by dispersing on a SiO2 support were made by the one-pot sol-gel method. Doping with W shifts the TiO2 band gap energy from 3.2 eV to around 3.06 eV. The surface area of the supported W-TiO2/SiO2 material was significantly increased, by approximately 3 times, in comparison to the bare TiO2. The photocatalytic activities of the catalysts were evaluated in the degradation reaction of p-nitrophenol in aqueous solution and basic medium. After 240 min of photodegradation, more than approximately 99% p-nitrophenol could be mineralized with the most active W-TiO2/SiO2 catalyst. Under UV irradiation, p-nitrophenol was initially photodegraded into hydroquinone and benzosemiquinone intermediates, which were further degraded into smaller fragments such as organic carboxylic acids and finally completely mineralized. A proposed photoreaction mechanism was presented based on the key roles of the surface hydroxyl species and superoxide radicals such as O2- and ⋅OH, together with W6+/W5+ couples and e-/h+ pairs in the catalysts in the p-nitrophenol photodegradation. The one-pot sol-gel synthesis method was proven to be effective to obtain W-TiO2/SiO2 catalyst with large surface area and high photocatalytic activity, and it can be also used for the preparation of other heterogeneous catalysts.